2019
DOI: 10.1002/adom.201900647
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Heteroepitaxial VO2/Mica Films with Extremely Low Optical Trigger Threshold and Large THz Field Modulation Depth

Abstract: More interestingly, the phase transition of VO 2 can be triggered by thermal, [7,8] electrical, [9,10] and optical stimuli [11][12][13][14][15][16] as well as strain, [17,18] making it very appealing to practical applications. Across the MIT, VO 2 changes from a monoclinic phase into a rutile phase. The insulating monoclinic phase has high THz transparency due to its low-density free carrier absorption, while the metallic rutile phase is opaque in the THz regime due to its high free carrier concentration (>10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Another approach involves introducing epitaxial strain to influence the microstructures of VO 2 film. This approach highly relies on epitaxial growth techniques and avoids the degradation of modulation phenomenon [ 129 ]. Other optimizations, such as the broadening of the phase transition temperature window [ 91 ] and anisotropic modulation [ 130 ], can also be realized by controlling the synthesis process of VO 2 film.…”
Section: Film Deposition and Property Optimizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Another approach involves introducing epitaxial strain to influence the microstructures of VO 2 film. This approach highly relies on epitaxial growth techniques and avoids the degradation of modulation phenomenon [ 129 ]. Other optimizations, such as the broadening of the phase transition temperature window [ 91 ] and anisotropic modulation [ 130 ], can also be realized by controlling the synthesis process of VO 2 film.…”
Section: Film Deposition and Property Optimizationmentioning
confidence: 99%
“…Except for ion doping, another effective approach to optimize the IMT properties is to alter the film structure through substrate influence. Recent research reported by Liang et al took a novel approach to reduce the excitation energy of ultrafast IMT [ 129 ]. They deposited Van der Waals (vdW) heteroepitaxial VO 2 film on ultrathin (~13 um) mica substrate.…”
Section: Film Deposition and Property Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This weak vdW bonding between the VO 2 film and the mica sheet does not induce any significant lattice strain in the VO 2 layer. Therefore, the VO 2 film behaves as a nearly freestanding film on the mica sheet, which enables MIT with exceedingly low energy stimuli [90]. Moreover, owing to the weak vdW bonding between adjacent mica sheets, the thin mica sheet can be peeled off from the substrate, creating transparent and flexible VO 2 (M)/mica sheets.…”
Section: Fabrication Of Flexible Monoclinic-phase Vo 2 (Vo 2 (M)) Films Via Chamber-based Depositionmentioning
confidence: 99%